Climate-smart villages: practical adaptation options to improve food security and resilience - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Climate change hits smallholder farmers hard. More variable weather patterns cause crops to fail, undermining livelihoods and food security. At the same time, farming generates greenhouse gases (GHGs) that contribute to the problem. What practical steps can smallholder farmers take to adapt their agriculture to secure the food supply? And might those mitigate emissions? In a search for answers the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is working with a vast range of partners to test an assortment of interventions in ‘climate-smart villages’.